Serum amyloid A-low-density-lipoprotein complex and mortality in patients with suspected or known coronary artery disease: the ANOX study. (3rd October 2022) - Suzuki, M; Kotani, K; Matsuda, M; Ajiro, Y; Shinozaki, T; Sakagami, S; Yonezawa, K; Shimizu, M; Funada, J; Takenaka, T; Wada, M; Abe, M; et al.
Abstract: Background: Serum amyloid A-low-density-lipoprotein (SAA-LDL) is a complex formed from the oxidative interaction between SAA and LDLs. A relatively small-scale study has shown that circulating SAA-LDL levels may serve as a prognostic marker in patients with stable coronary artery disease (CAD). However, the prognostic value of SAA-LDL should be confirmed in a larger-scale cohort study. Methods: Using data from a multicenter, prospective cohort of 2416 patients with suspected or known CAD enrolled in the ANOX (Development of Novel Biomarkers Related to Angiogenesis or Oxidative Stress to Predict Cardiovascular Events) study, we assessed the prognostic value of serum levels of SAA-LDL. The primary outcome was all-cause death. The secondary outcomes were cardiovascular death and major adverse cardiovascular events (MACE) defined as a composite of cardiovascular death, nonfatal myocardial infarction, and nonfatal stroke. Patients were followed up over 3 years. Results: Stepwise regression analysis including baseline data on potential clinical confounders (i.e., age, sex, body mass index, hypertension, dyslipidemia, diabetes, current smoking, estimated glomerular filtration rate, the Gensini score, previous myocardial infarction, previous stroke, previous heart failure hospitalization, atrial fibrillation, malignancies, anemia, antihypertensive drug use, statin use, and aspirin use) and established cardiovascular biomarkers (i.e., N-terminal pro-brain natriuretic peptide, high-sensitivity cardiac troponin I [hs-cTnI], and high-sensitivity C-reactive protein [hs-CRP]) revealed that independent determinants of SAA-LDL levels were female sex, dyslipidemia, the Gensini score, absence of statin use, hs-cTnI, and hs-CRP. After adjusting for potential clinical confounders and established cardiovascular biomarkers, the highest quartile of SAA-LDL levels (vs. the lowest quartile) was significantly associated with the incidence of all-cause death (hazard ratio [HR], 1.51; 95% confidence interval [CI], 1.02–2.26), but not with that of cardiovascular death (HR, 1.11; 95% CI, 0.59–2.10) or MACE (HR, 1.57; 95% CI, 0.97–2.57). Stratified analyses revealed that this association was pronounced in patients with low hs-cTnI (<75th percentile) (HR, 1.85; 95% CI, 1.06–3.30) and in patients with low hs-CRP levels (≤1.0 mg/L) (HR, 2.30; 95% CI, 1.17–4.79). Conclusions: Elevated SAA-LDL levels were independently associated with the risk of all-cause death in patients with suspected or known CAD. The SAA-LDL level appears to serve as a prognostic biomarker for risk stratification in relatively low-risk patients with low hs-cTnI (<75th percentile) or low hs-CRP (≤1.0 mg/L). Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The ANOX study is supported by a Grant-in-Aid for Clinical Research from the National Hospital Organization.